Analyzing intelligence : national security practitioners' perspectives - George, Roger Z., 1949-; Bruce, James B. (Georgetown University Press, 2014)
Analyzing Intelligence, now in a revised and extensively updated second edition, assesses the state of the profession of intelligence analysis from the practitioners point of view. The contributors-most of whom have held senior positions in the US intelligence community-review the evolution of the field, the rise of new challenges, pitfalls in analysis, and the lessons from new training and techniques designed to deal with 21st century national security problems. This second edition updates this indispensable book with new chapters that highlight advances in applying more analytic rigor to an.